Comprehensive evolutionary analysis of the TCP gene family: Further insights for its origin, expansion, and diversification - Wang, Jun-Li; Wang, Hong-Wei; Cao, Ya-Nan; Kan, Sheng-Long; Liu, Yan-Yan (Frontiers in Plant Science, 2022)
TCP proteins are plant-specific transcription factors, which are involved in a broad range of physiological processes of plant growth and development. However, the origin and evolutionary history of this gene family is not fully depicted. Here, we present a genome-wide survey of TCP genes in 59 species (including 42 genomes and 17 transcriptomes) covering all main lineages of green plants, and also reconstruct the evolutionary history of this gene family. Our results suggested that the origin of TCP genes predates the emergence of land plants, possibly in the common ancestor of Charophyta, Zygnemophyta and Embryophyta. The TCP gene family gradually experienced a continuous expansion and grew from a few members in algae, moss and lycophytes to dozens, and sometimes over fifty members in angiosperms. Phylogenetic analysis indicated that at least four subclades (Class I and three subclades of Class II) have been occurred in the ancestor of spermatophyte. Both dispersed duplication and segmental duplication/or whole-genome duplication (WGD) contributed significantly to the expansion of the TCP gene family over the course of evolution. Our findings provide a comprehensive evolutionary analysis of the TCP gene family and highlight the importance of gene duplications in the evolution of this plant-specific transcription factors.